O estágio supervisionado na formação do professor: das ciências das religiões ao ensino religioso - Guedes, Thiago Rafael Soares de Souza (2019)
This study, as part of its central objective, sought to investigate the perspectives of Supervised Internship in teaching, more specifically regarding the process of building the professional identity of being a teacher of Religious Education. As part of the specific objective we considered the link between theory / practice and implications about the Supervised Internship in the Degree in Religious Sciences in the context of UFPB. In this sense, the historical rescue about the Supervised Internship in Brazil was prioritized, as well as the technical, legal and pedagogical aspects of it, thus being a chain of requirements, prerogatives and precepts for the interns, as well as for the entities. of higher education and school establishments, where the internship takes place and its contributions to the future of the profession and to be a teacher of Religious Education. As a methodology, the investigative course was developed from the possibilities of the theoretical revision, of bibliographic-documental nature, under a qualitative exploratory approach. As theoretical frameworks were used Sérgio Junqueira, João Décio Passos, Francisco Imbernón, among others. In conclusion, it was found that there is a greater participation of the faculty of the undergraduate degree in Religious Sciences of UFPB, in order to minimize or even curb the dissonance between the universe of theory and practice, as well as articulate the curriculum to the Pedagogical Political Project of the course, the Common National Curriculum Base and the National Guidelines for the Science of Religion course.